A dilution effect in the emerging amphibian pathogen Batrachochytrium dendrobatidis - Searle, Catherine L. (National Academy of Sciences, 2011)
Global declines in biodiversity are altering disease dynamics in complex and multifaceted ways. Changes in biodiversity can have several outcomes on disease risk, including dilution and amplification effects, both of which can have a profound influence on the effects of disease in a community. The dilution effect occurs when biodiversity and disease risk are inversely related, whereas the amplification effect is a positive relationship between biodiversity and disease risk. We tested these effects with an emerging fungal pathogen of amphibians, Batrachochytrium dendrobatidis (Bd), which is responsible for catastrophic amphibian population declines and extinctions worldwide. Despite the rapid and continued spread of Bd, the influence of host diversity on Bd dynamics remains unknown. We experimentally manipulated host diversity and density in the presence of Bd and found a dilution effect where increased species richness reduced disease risk, even when accounting for changes in density. These results demonstrate the general importance of incorporating community structure into studies of disease dynamics and have implications for the effects of Bd in ecosystems that differ in biodiversity.